The Implementation of Occupational Health and Safety for Pregnant Workers in Various Workplaces - Atidira Dwi Hanani (Indonesian Journal of Applied Research (IJAR), 2021)
Pregnant workers have more health risks for health problems than other workers. There are different potential hazards in different workplaces. Occupational Health and Safety Programs need to be implemented for pregnant workers in order to avoid work related diseases in various workplaces. This study aims to determine the the implementation of occupational health and safety for pregnant workers in various workplaces. This study uses a qualitative method by conducting FGD (Focus Group Discussion) with pregnant women workers from various workplaces and in-depth interviews with occupational health and safety experts. Occupational health and safety programs have been implemented for pregnant workers such as the right to maternity leave, working hours arrangements, health insurance, and special protection for pregnant workers. However, there are some workplaces that still do not provide special protection for pregnant workers. Every workplace should pay more attention to the health and safety of pregnant workers as an effort to prevent occupational accidents and work related diseases